The wonderful wizard of oz - Baum, L. Frank (United Kingdom: Transatlantic press book, 2012)
When a cyclone hits the Kansas farm where Dorothy lives with her uncle Henry and aunt Em, she an=d her dog Toto are swept into the air and deposited in the strange, magical land of Oz. Her only hope of returning home is to seek the help of the all-powerful great Wizard, who lives in the Emerald City. Dorothy sets off along the yellow brick road that leads to the city, and on the way teams up with the Scarecrow, Tin Woodman and Cowardly Lion, who have their own wishes they would like the wizard to grant. One of the best loved fantasy adventures, the wonderful Wizard of Oz has enthralled generations of children. Its timeless appeal is a mark of how L. Frank Baum succeeded in his stated aim: to write "a modernized fairy tale, in which the wonderment and joy are retianed and the heartaches and nightmares are left out".
Location: 3C
Keywords: Fiction book